2018
DOI: 10.6028/nist.tn.2022
|View full text |Cite
|
Sign up to set email alerts
|

Pool boiling of HFO-1336mzz(Z) on a reentrant cavity surface; extensive measurement and analysis

Abstract: This paper quantifies the pool boiling performance of R1336mzz(Z), and R123 on a flattened, horizontal Turbo-ESP surface for heat fluxes between roughly 10 kWm-2 and 120 kWm-2. The study showed that the boiling performance of R1336mzz(Z) on the Turbo-ESP did not differ statistically from that of R123 for heat fluxes between 13 kWm-2 and 59 kWm-2. For heat fluxes larger than 59 kWm-2 , the R123 boiling heat flux was up to 5 % larger than the heat flux for R1336mzz(Z). For heat fluxes between 4 kWm-2 and 13 kWm-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…More recently, Kedzierski and Lin [73] measured a novel HFO refrigerant for heat recovery and air-conditioning applications, R1336mzz(Z), on a flattened, horizontal Turbo-ESP surface for heat fluxes between roughly 10 kW/m 2 and 120 kW/m 2 . The study showed that the boiling performance of R1336mzz(Z) on the TurboESP did not differ statistically from that of R123 for heat fluxes between 13 kW/m 2 and 59 kW/m 2 .…”
Section: Measurements For Low-gwp Refrigerants On Enhanced Surfacesmentioning
confidence: 99%
“…More recently, Kedzierski and Lin [73] measured a novel HFO refrigerant for heat recovery and air-conditioning applications, R1336mzz(Z), on a flattened, horizontal Turbo-ESP surface for heat fluxes between roughly 10 kW/m 2 and 120 kW/m 2 . The study showed that the boiling performance of R1336mzz(Z) on the TurboESP did not differ statistically from that of R123 for heat fluxes between 13 kW/m 2 and 59 kW/m 2 .…”
Section: Measurements For Low-gwp Refrigerants On Enhanced Surfacesmentioning
confidence: 99%